ANALYSIS OF RESEARCH METHODS OF SEGREGATION PROCESSES IN BULK MATERIALS - Paziuk, Mikhailo; Ovchynnykova, Iryna; Barishenko, Olena; Yerofieieva, Alina (Scientific Journal "Metallurgy", 2024)
The article is devoted to the analysis of methods of studying segregation processes in loose materials with the aim of creating a given segregation. The main idea is that the correct management of the segregation process leads to the improvement of the sintering process of the agglomerate and the saving of energy resources. The authors discuss different approaches to the study of segregation processes and their impact on the quality of the final product. Sintering ore fines on a grate by drawing air through a layer of sintering charge is the most common method of sintering. At the same time, it was determined that the characteristic features of the agglomeration process are preserved regardless of the design of the agglomeration machines. The model describing the performance of the sintering machine was considered and it was concluded that the increase in the performance of sintering machines at the operating sinter plant can be reduced to an increase in the vertical speed of sintering and the output of the finished agglomerate. Special attention is paid to methods that contribute to the prevention of undesirable phenomena in the process of segregation and optimization of this process to achieve the desired result. Thus, the increase in productivity is also associated with a decrease in downtime of the sintering machine. Models of layer formation with different approaches to the movement of individual particles of the charge are considered. Analysis of the obtained dependencies and comparison of the results of mathematical modeling with real processes allows us to conclude that the main influence on the process of formation of a layer of polydisperse material is provided by its physical and mechanical properties and the angle of inclination of the loading tray. Consideration of this topic in the article is of practical and economic importance for manufacturing enterprises engaged in the processing of loose materials. In general, the article is an important contribution to the study of segregation processes and their impact on production processes.